2010
DOI: 10.1242/dev.051375
|View full text |Cite
|
Sign up to set email alerts
|

Functional full-term placentas formed from parthenogenetic embryos using serial nuclear transfer

Abstract: SUMMARYMammalian parthenogenetic embryos invariably die in mid-gestation from imprinted gene defects and placental hypoplasia. Based on chimera experiments, trophoblastic proliferation is supposed to be inhibited in the absence of a male genome. Here, we show that parthenogenetic mouse embryonic cell nuclei can be reprogrammed by serial rounds of nuclear transfer without using any genetic modification. The durations of survival in uteri of cloned foetuses derived from green fluorescent protein (GFP)-labelled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In vitro culture of B-ESCs and P-ESCs can lead to alterations in DNA methylation and covalent modifications of histones such as histone acetylation and methylation [19,33,[45][46][47][48]. Moreover, in P-ESCs the expression of several imprinted genes is altered due to absence of a paternal chromosomal complement [19,46,47].…”
Section: Alteration Of Key Imprinted Genes In P-escsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro culture of B-ESCs and P-ESCs can lead to alterations in DNA methylation and covalent modifications of histones such as histone acetylation and methylation [19,33,[45][46][47][48]. Moreover, in P-ESCs the expression of several imprinted genes is altered due to absence of a paternal chromosomal complement [19,46,47].…”
Section: Alteration Of Key Imprinted Genes In P-escsmentioning
confidence: 99%
“…The efficiency of full-term development significantly increases when the H19/Igf2 DMR together with the DMR found within a second imprinted gene cluster Dlk1/Dio3 on chromosome 12 are deleted [23,32]. Most recently Hikichi et al showed that the development of PG embryos can be extended following serial nuclear transfer (NT) and is associated with a decrease in H19 expression [33]. Altogether, these results suggest that the correct expression of H19 is important for normal embryonic development.…”
mentioning
confidence: 99%
“…Hikichi and co-workers established a new type of pESCs by transferring traditional ESC nuclei into oocytes and deriving these pESCs again at the blastocyst stage (NT-pES), leading to two to five times enhancement of differentiation ability, compared with the original pESCs [ 29 ]. The same group reported development of parthenogenetic embryos to term using the serial nuclear transfer method [ 30 ]. Epigenetic modification was evidently altered during reprogramming mediated by nuclear transfer, and aberrant methylation observed in cloned embryos and animals.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the chimeras from aES cells had skeletal abnormality and other defects [10,23], and no chimeras were generated from two mature sperms derived aES cells assisted with SCNT previously. Some labs tried to erase the strict imprinting of uniparental ES cells by serial nuclear transfer method [24] or long-term cell culture [25]. But these methods were either complicated or time-consuming.…”
Section: Discussionmentioning
confidence: 99%